Data Security and Protection - A. J., Geetha (Indian Journal of Computer Science, 2023)
Greater the dependency on computers and other digital devices, greater is the potential risk of data theft and loss. Databases are one of the important valuable assets of any organisation. The present paper analyzes the concept of data protection, breach of data security, significance of data protection, and ways to safeguarding the data. The protection laws prevailing in India and need of implementing a comprehensive legal backup is discussed in the present paper.